PARTICULATE DELIVERY SYSTEM OF CHITOSAN - DITERPENE LACTONE FRACTION OF SAMBILOTO (ANDROGRAPHIS PANICULATA NEES): PREPARATION, CHARACTERIZATION AND IN VITRO DRUG RELEASE - Sari, Retno; Soeratri, Widji; Hendradi, Esti (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This paper was aimed to study the effect of chitosan, sodium tripolyphosphate (TPP) as crosslinker, and diterpene lactone fraction of sambiloto (FDTL) from Andrographis paniculata Nees which contained 75.9% andrographolide on the characteristics of the FDTL-chitosan particulate system. Those characteristics were the physicochemical interaction, physical state, morphology, and drug entrapment efficiency. The in vitro drug release of the selected FDTL-chitosan particulate system was also evaluated. Methods: The particulate system of FDTL-chitosan was prepared by ionic gelationâ€“spray drying method with the various amounts of TPP, chitosan, and FDTL. The physical characteristics were evaluated using Fourier transform infrared (FTIR), differential thermal analyzer (DTA), and X-ray diffraction, scanning electron microscope. In vitro drug release was performed in 0.1% sodium lauryl sulfate media at 37Â°C. Results: The results of FTIR and DTA analysis were in accordance with the results of morphology evaluation which indicated that chitosan-TPP ratio 10:8 could produce chitosan particles with a spherical and smooth surface. FDTL has been trapped in chitosan particulate systems, and the crystallinity of FDTL changed. Particulate systems with FDTL-chitosan-TPP ratio - 4:10:8 showed better characteristics compared to others with entrapment efficiency of 33.82%. The dissolution efficiency at 360 minutes (ED360) of particulate systems FDTL-chitosan was higher up to 1.5 times compared to FDTL. Conclusion: The difference in the ratio of chitosan and TPP affected the morphology of chitosan particles since the amount of drug loaded, and the amount of chitosan affected the drug entrapment. The ED360 of FDTL of FDTL-chitosan-TPP increased up to 1.5 times compared to the FDTL.